DAMPAK SHARING KNOWLEDGE TERHADAP BEST OPERATIONAL PRACTICE MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN SERVICE QUALITY DI POLWILTABES SURABAYA - Zeplin Jiwa Husada Tarigan; Wahju Astjarjo Rini; Sundring Pantja Djati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
Sharing Knowledge is originated from the interaction between individuals which will form a group or working group in a company, while the working group with expertise/skills is called teamwork. The working group should be developed to be able to communicate and have good relationships within the department, between departments and between organizations. Good communication within the organization will improve the working relationship to be more intense and faster. There are no boundaries either between individuals or individuals and departments in the organization so as to create an effective working relationship and a strong team work which lead to the creation of the best practices operational. Based on the survey by interviewing and spreading questionnaires to 266 police members of the police in POLWILTABES SURABAYA about sharing knowledge of best operational practices (BOP) in the police organization through team work's affectivity and OCB (organizational citizenship behavior). The results showed that sharing knowledge does not directly impact organizational citizenship behavior as an organizational culture, but it is indirectly give impact through the team work's affectivity moderator variable. Sharing knowledge as an organizational culture has an impact on enhancing the effectiveness of team work. The Effectiveness of team work influence organizational citizenship behavior in police organizations to increase the best operational practice. Team work's affectivity has influence towards Best Operational Practices (BOP) in the police organization. OCB (Organizational citizenship behavior) also has influence towards the best operational practices (BOP) in the police organization.